Mechanochemical ablation in patients with chronic venous disease: A prospective multicenter report. (July 2014) - Bishawi, M; Bernstein, R; Boter, M; Draughn, D; Gould, CF; Hamilton, C; Koziarski, J
Background: There are several endovenous methods to ablate the saphenous vein, all of which require tumescent anesthesia. This report was designed to evaluate the efficacy of a tumescent-free technique using mechanochemical ablation (MOCA). Methods: This was a prospective observational multicenter report on the efficacy of MOCA in selected patients with lower extremity chronic venous disease. Demographic information, clinical and procedural data were collected on a customized database. The distribution and extent of venous reflux and the closure rate of the treated veins were assessed with duplex ultrasound. Pain was evaluated during the procedure and postoperatively using an analog scale. The presence and severity of complications were recorded. Patient improvement was assessed by clinical-etiology-anatomy-pathophysiology (CEAP) class and venous clinical severity score (VCSS). Results: There were 126 patients that were included at baseline, 81% females, with a mean age of 65.5 ± 14 years. The average BMI was 30.5 ± 6. The mean diameter of the great saphenous vein in the upper thigh was 7.3 mm and the mean treatment length was 38 cm. Adjunctive treatment of the varicosities was performed in 11% of patients during the procedure. Closure rates were 100% at one week, 98% at three months, and 94% at six months. Post-procedure complications included hematoma 1%, ecchymosis 9%, and thrombophlebitis 10%. There were no cases of venous thromboembolism. There was significant improvement in VCSS ( p < 0.001) for all time intervals. Conclusion: MOCA of the saphenous veins has the advantage of endovenous ablation without tumescent anesthesia, making it an almost pain-free procedure. High occlusion rates with significant clinical improvement can be achieved with this method at short term.